Surface analysis of semiconductors and simulation using Python - Menon, Krishnanunni (Nanyang Technological University, 2022)
Reflection High Energy Electron Diffraction (RHEED) is a technique that is employed to study the surface structures of crystalline materials on a substrate. It is primarily used for monitoring real time growth information not limited to growth rate, thickness, surface evenness and so on. RHEED analysis derives information based on patterns such as streaks created from the reflection diffraction of the surface by an electron gun . RHEED images are then characterized based on its spacing and shape of the streak patterns. GaN polar and N polar High Electron Mobility Transistor (HEMT ) are two types of thin film growth structures used in this work to study reflection diffraction patterns. The patterns generated are further analyzed to obtain diffraction streak spacing and Lattice Constant These reflection diffraction patterns, and its properties are studied through a simulation software created using Python programming. By plotting a cross sectional line a cross RHEED images the intra row spacing and Lattice Constant of the grown semiconductor film based on calibration values determined prior can be determined. The values could then be studied to understand the stress in the film and possible quality of the material